Photodynamic therapy using topical 5‐aminolaevulinic acid vs. surgery for basal cell carcinoma. (28th June 2012) - Cosgarea, R.; Susan, M.; Crisan, M.; Senila, S.
Abstract: Background  Photodynamic therapy (PDT) is an attractive modality for the treatment of BCC, based on its generally favorable efficacy, adverse effect profile and its excellent cosmetic outcome. Objectives  The purpose of the study is to compare the efficacy and cosmetic outcome of photodynamic therapy with topical 5‐aminolaevulinic acid (ALA‐PDT) vs. simple excision surgery for superficial and nodular basal cell carcinoma (BCC). Methods  A total of 72 patients, 32 with 48 lesions, were treated with ALA‐ PDT, and 40 with 46 lesions treated by excision were included in this prospective, comparative, controlled, clinical study. The patients have been followed for 16–37 months (mean 25 months). The PDT was performed in combination with 5‐aminolaevulinic acid twice, one month apart. Surgical excision was performed under local anesthesia with a 3‐mm margin, followed by histological examination. The cosmetic outcome was evaluated by the physician according to a 4‐point scale. Results  Overall 94 BCC were treated. Complete healing rates did not differ significantly between groups, P  = 0.64 (46/48 [95.83%] lesions treated with PDT vs. 44/46 [95.65%] lesions with surgery). In the first 12 months of follow‐up, 4 lesions had recurred, 2 of which were in the PDT group while 2 lesions after surgery. The mean follow‐up was 25 months. The recurrence rate in the ALA‐PDT group was 4.16% vs. 4.34% in the surgery group, p = 0.64. The cosmetic outcome was superior for ALA‐PDT at all time points. At 12 months, 100% lesions treated with ALA‐PDT had an excellent or good cosmetic outcome, according to the investigator, compared with 88.86% with surgery, P  = 0.01. Conclusion  ALA‐PDT offers a similarly high efficacy, and a better cosmetic outcome than simple excision surgery in the treatment of BCC.